Plus-sized misadventures in love! 1 : Positive thinking - Mamakari (Plus-sized misadventures in love!, 2025)
All Yumeko ever saw were her flaws. Her unhappy outlook infected not just her, but everyone around her, too. It's only after a car accident that leaves Yumeko with amnesia that she wakes up with a brand-new lease on life, one that attracts all kinds of adventures and maybe even love.